DIPLOMATIC ACTIVITIES OF CELALEDDIN ARIF BEY DURING THE NATIONAL STRUGGLE PERIOD (Third Sector Social Economic Review, 2025)
No war in the modern sense is won only at the front. Equally important activities took place behind the front and outside the country. As a matter of fact, diplomatic initiatives also occupied an important place during the National Struggle. Being aware of this situation, the Ankara Government attached importance to diplomatic activities and appointed representatives from TBMM members, officers to European capitals. Thanks to these people, in addition to diplomatic support, the supply of war ammunition necessary for the National Struggle was ensured. In addition, propaganda activities were carried out on the fronts and in the international arena. This study focuses on the activities of Celaleddin Arif Bey, who served as the second president of the Grand National Assembly of Turkey, Deputy Minister of Justice and Representative to Rome during the National Struggle. In this context, Arif Bey’s diplomatic activities since his participation in the National Struggle, about which there are very rare studies in the literature, were analyzed. Document analysis technique, one of the qualitative research methods, was used in the study. The study is based on archival documents available in Turkey. In addition, periodicals and research works were also utilized. The findings obtained as a result of the document analysis conducted in the light of qualitative data showed that Arif Bey, with his diplomatic skills and patriotism, defended Turkey's rights despite the difficulties and carried out active activities to obtain the necessary support.
Keywords: Celaleddin Arif Bey; Diplomacy; Diplomacy during the National Struggle Period; Propaganda Activities; Intelligence Operations